Abdominal Lymphangioma and Hemangioma in a Newborn - Charikleia D. Demiri; Christos Kaselas; Dimitrios Godosis; Andreas Neofytou; Ioannis Spyridakis (Case Reports in Pediatrics)
Abdominal hemangiolymphangioma (HLA) in neonates is a rare condition that demands surgical intervention after a complete preoperative diagnostic approach. The differential diagnosis and the establishment of a therapeutic algorithm is a challenge, both for the neonatologists and the pediatric surgeons, because there is no consensus in the management of HLAs in infancy according to the literature. We report a rare case of abdominal HLA in a female newborn that was admitted to our pediatric surgery department with a prenatal diagnosis of an abdominal cystic tumor. After a thorough preoperative diagnostic approach, the neonate underwent an explorative laparotomy and lesion excision with simultaneous splenectomy due to the operative findings. The neonate had an uncomplicated postoperative period and is free of recurrence a year after. Only the pathology examination can reveal the HLA diagnosis. When a total surgical excision is evitable, a close follow-up follows an uncomplicated postoperative hospitalization.